Tingkat Kematangan Karir Pada Pelajar SMA Ditinjau Dari Perbedaan Jenis Kelamin - Oktavia, Siska; Purbaning, Prias Hayu (SOLUTION, 2023)
This study aims to: (1) know the level of career maturity at the students of class XI SMA BOPKRI 2 Yogyakarta. (2) Know the level of career maturity between men and women. (3) Know the scores that are identified in the category are undercover maternity career. This type of research uses quantitative descriptive research. Subjects in this study are students of class XI SMA BOPKRI 2 Yogyakarta which is a sample of 56 students. The sample technique used in this study used purposive sampling technique. The data collection technique used a questionnaire regarding career maturity level and 42 valid items were found. The questionnaire is made based on the supervisory maturity aspect of the Super (Uman Suherman, 2009), namely (1) career planning (2) career exploration (3) Knowledge of making decisions (4) knowledge of the world of work (5) knowledge of preferred job groups (6) Realization of career decisions and (7) Career orientation. The value of the reliability coefficient using Cronbach Alpha is 0.859. The results of this study indicate that generally students of class XI SMA BOPKRI 2 Yogyakarta has a very high career maturity level seen in scores above 136.5. At the level of career maturity between men and women students not found significant differencesin proven value p 0.067 0.05. Meanwhile, 24 male students (100%) and 32 female students (100%) have a very high career maturity level. There are no men and women students who have high levels of career, medium, low and lower career. The results of the categorization analysis of the existing there are 11 instrument items with a career maturity level is by 26%.